SOME MISCELLANEOUS EXPERIMENTS WITH COCONUT EMBRYO CULTURE - Roger Ashburner; D.R. Tomlinson; W.K. Thompson (International Coconut Community, 1996)
The growth and development of coconut embryo cultures can be manipulated by various methods, including the alteration of the carbon source in the basal medium. Shoot growth was favoured when glucose was used as the carbon source, but root growth was stimulated when sucrose was used at equimolar concentrations. Both fructose and glucose were found to, stimulate vitrification and mannitol was inert. BAP had no effect on the growth and development of coconut embryo cultures up to a level of 316 M. Ethylene and carbon dioxide built up in the culture flasks to biologically active concentrations but did not affect growth in the time period measured. The build‑up of these gases could be alleviated through altering the sealing mechanisms of the culture flasks. In vitro, coconut embryos germinate faster in sealed culture flasks and it is assumed that this is to do with the gaseous composition of the headspace. Genotype of the embryo has perhaps the greatest influence on coconut growth and development in vitro, with significant differences being found in the growth rates of the 10 Pacific genotypes tested. This issue should be taken into account when recommendations are made on the use of a general protocal for the use of coconut embryo culture for the collection and conservation of germplasm.